2016
DOI: 10.1051/radiopro/2016020
|View full text |Cite
|
Sign up to set email alerts
|

Health check-ups of children living in a Belarus district contaminated after the Chernobyl accident

Abstract: -The Chernobyl nuclear accident, which occurred on April 26th, 1986, resulted in widespread long-term contamination, mainly due to 137 Cs, of large territories where populations live. A project was initiated to assess the 137 Cs body burden and health status, not limited to radiation-induced pathologies, for all children living in a highly contaminated district in Belarus; the aim was to provide detailed information for parents worried about their children's health, without the intention of quantifying the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Health impacts of changes in lifestyle associated with protective actions (40) In addition to radiation-induced health effects following the accident, there may be other health-related impacts due to changes in lifestyle attributable to the presence of radioactivity and the actions taken to avoid radiation exposure. Many studies carried out following the Chernobyl and Fukushima nuclear accidents have reported a range of physical and psychological disorders linked to the protective actions taken not only during the early phase, but also during the intermediate and long-term phases (Hasegawa et al, 2015;Luccioni et al, 2016).…”
Section: Psychological Consequencesmentioning
confidence: 99%
“…Health impacts of changes in lifestyle associated with protective actions (40) In addition to radiation-induced health effects following the accident, there may be other health-related impacts due to changes in lifestyle attributable to the presence of radioactivity and the actions taken to avoid radiation exposure. Many studies carried out following the Chernobyl and Fukushima nuclear accidents have reported a range of physical and psychological disorders linked to the protective actions taken not only during the early phase, but also during the intermediate and long-term phases (Hasegawa et al, 2015;Luccioni et al, 2016).…”
Section: Psychological Consequencesmentioning
confidence: 99%